Comparison of intravenous versus combined oral and intravenous antimicrobial prophylaxis (COMBINE) for the prevention of surgical site infection in elective colorectal surgery: study protocol for a multicentre, double-blind, randomised controlled clinical trial. Issue 4 (12th April 2018) - Vignaud, Marie; Paugam-Burtz, Catherine; Garot, Matthias; Jaber, Samir; Slim, Karem; Panis, Yves; Lucet, Jean-Christophe; Bourdier, Justine; Morand, Dominique; Pereira, Bruno; Futier, Emmanuel
Abstract : Introduction: Surgical site infections (SSIs) account for 30% of all healthcare-associated infections, with reported rates ranging from 8% and 30% after colorectal surgery and are associated with increased morbidity and mortality rates, length of hospital stay and costs in healthcare. Administration of systemic antimicrobial prophylaxis before surgery is recommended to reduce the risk of SSI, but the optimal regimen remains unclear. We aim to evaluate whether a combined oral and intravenous antimicrobial prophylaxis could be more effective to reduce the incidence of SSI after colorectal surgery, as compared with the standard practice of intravenous antimicrobial prophylaxis alone. Methods and analysis: Comparison of intravenous versus combined oral and intravenous antimicrobial prophylaxis (COMBINE) trial is a randomised, placebo-controlled, parallel, double-blind, multicentre study of 960 patients undergoing elective colorectal surgery. Patients will be randomly allocated in a 1:1 ratio to receive either combined oral and intravenous antimicrobial prophylaxis or intravenous antibiotic prophylaxis alone, stratified by centre, the surgical procedure (laparoscopic or open surgery) and according to the surgical skin antisepsis (chlorexidine–alcohol or povidione-iodine alcoholic solution). The primary endpoint is the rate of SSI by day 30 following surgery, with SSI defined by the criteria developed by the Centers for Disease Control and Prevention. Data will be analysed on the intention-to-treat principle and a per-protocol basis. Ethics and dissemination: COMBINE trial has been approved by an independent ethics committee for all study centres. Participant recruitment began in May 2016. Results will be published in international peer-reviewed medical journals. Trial registration number: EudraCT 2015-002559-84; NCT02618720 .